PENGARUH FAKTOR HIDRODINAMIKA TERHADAP SEBARAN LIMBAH AIR PANAS DI LAUT - Dewi Surinati; Muhammad Ramadhani Marfatah (OSEANA, 2019)
HYDRODYNAMICS EFFECT TO THE DISTRIBUTION OF THERMAL WASTE IN THE OCEAN. The ocean is a thermal waste disposal site derived from thermal power plants. The ecosystems and marine biota could be disrupted even massive damaged if this waste was disposed into the ocean without proper processing. All activities in the ocean need a well understanding of hydrodynamics to avoid or minimize any negative effects that may occur. It needs dispersion modeling of heat water prior to the construction of the power plant in order to reduce the impact of environmental damage.